Camerobia and Neophyllobius (Acari: Prostigmata: Camerobiidae) from Australia, with the descriptions of two new species - Fan, Qing-Hai; Walter, David E. (Zootaxa, 2006)
We review the mites of the genera Camerobia and Neophyllobius (Acari: Prostigmata: Camerobiidae) from Australia and propose two new species, Neophyllobius variegata from soil under rocks in The Northern Territory, and N. womersleyi from under bark in Adelaide, South Australia. Two known species, Camerobia australis Southcott and Neophyllobius ornatus Womersley, are redescribed and new data are provided. A key to the described species of Camerobiidae known from Australia and an updated list of Neophyllobius species described since 1991 are provided.